Progress and Trends in Forage Cactus Silage Research: A Bibliometric Perspective - Stéfani A. Santos; Hortência E. P. Santana; Meirielly S. Jesus; Iran Alves Torquato; Joana Santos; Preciosa Pires; Denise Santos Ruzene; Daniel Pereira Silva (Fermentation)
Opuntia spp. (forage cactus or spineless cactus) is a plant native to Mexico that is commonly used as alternative nutrient-rich fodder in semi-arid regions. Due to its resistance to drought, forage cactus has become an important least-cost ingredient for formulating balanced rations for ruminants during times of scarcity. In addition, ensiling, an anaerobic fermentation process, is also a strategy used to allow a supply of bulky food all year round, since it conserves forage and maintains its nutritional value. In this sense, using the Scopus database and the visualization tool VOSviewer, the present work proposes a bibliometric analysis of forage cactus silage to track and map the evolution and main issues in the research field, current trends, and future directions. The results revealed that the first publication was in 2013; and since 2020, the number of publications has been growing. Brazil was highlighted, by far, as the most relevant country on the topic, and the top institutions were from northeast Brazil, which has been working on co-authored articles. The current hot research topics are focusing on the mixed silage of forage cactus and other forages such as gliricidia, maniçoba, and sorghum biomass, as well as evaluating the fermentative performance and chemical characteristics for improving ruminal diets, especially for goats and sheep. This study provides important information for researchers to identify gaps and direct their studies to better use the whole potential of forage cactus as an alternative roughage source.